A comparison between two solution approaches for diaphragm-based capacitive pressure microsensor - Faris, Waleed Fekry; Mohammed, Hazem (2004)
We formulated the problem of a capacitive pressure microsensor using linear plate model. Then, we solved the problem using two approaches; the first is analytical approach and the second is a reduced-order model using four-term Galerkin approximation employing polynomial expansion. We found that the pull-in value of the capacitance vary widely between the two approaches almost 40 percent increase in the second method. Also, central deflection at which the pull-in takes place is different between the two methods